Makna “Pacaran Syar’i” pada Film Cinta Subuh - Lovina Fernando, Giska; Akhmad Rifa'i (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Many discourses in social life are found, one of which is the discourse of